RK-HO-FDTD Scheme for Solving Time-dependent Schrodinger Equation - Zhu, Min; Wang, Yi (Applied Computational Electromagnetics Society Journal (ACES), 2021)
The Runge-Kutta high-order finite-difference time-domain (RK-HO-FDTD) method is adopted to solve the time-dependent Schrodinger equation. The update equations of the RK-HO-FDTD method have been presented for wave function. The simulation results of the 1D potential well strongly confirm the advantages of the RK-HO-FDTD scheme over the conventional FDTD.